Corrosion of alloys used in dentistry: A review - Upadhyay D.; Panchal M.A.; Dubey R.S.; Srivastava V.K. (My University, 2025)
For regaining the normal functions of the dentition, artificial materials are often used to restore the missing part or structure, these are known as dental materials. Metals and alloys, e.g., gold alloys are commonly used dental materials, due to their high strength and other desirable properties. Due to high cost of gold, alloys are being increasingly used in dental applications. Many substitutes for gold alloys have also been employed and some of them possess superior mechanical properties. Increasing knowledge about interaction of dental materials with oral tissues has resulted in evolution of high performance dental materials to meet the various requirements of the oral environment. Leaching of metallic ions and food habits are the main cause of corrosion of metallic dental implants and restorations. Therefore, corrosion has been considered as the most important factor in the selection of metallic materials, hence it deserves special emphasis and must be evaluated in ever-changing oral environment. The main objective of the present review is to describe the importance of corrosion of dental metals and alloys. Different dental materials together with oral environments and various types of corrosion have been described and related reported findings have also been reviewed briefly. © 2006.